Analysis of the application of recycled polypropylene: a case study in the refrigeration segment in south of Brazil - Kohlbeck, Eloiza; Beuren, Fernanda Hänsch; Santos, Vanessa Maria (Brazilian Journal of Operations & Production Management, 2023)
Goal: Analyze the benefits of the application of recycled polypropylene in the evaporation tray of refrigerators in a multinational company of electro-electronic equipment. Design / Methodology / Approach: This research conducts a systematic literature review; performs a Life Cycle Analysis (LCA) of the polypropylene production, interpreting its results through a Pareto Diagram; and presents a case study in a multinational company of white line electro-electronic equipment. Results: The LCA results point out that propylene and the components released by the chemical plant cause the main negative externalities under the environment and human health, so that during PP production, propylene is responsible for 72% of the impacts under global warming and 86% in the face of scarcity of fossil resources. Thus, the case study proposes recycling polypropylene, following the Circular Economy guidelines by aligning the proposal with the Zero Waste policy, with modular design, with Reverse Logistics, and with Sustainable Development Goals. Research limitations: The work presents limitations inherent to literature review works, where filters are used to limit the search (limited to articles, published between 2012 and 2021 and written in English). Practical implications: The research encourages recycling, pointing out its contribution under the environmental, social and economic spheres. Originality / Value: The research presents originality and methodological value by combining qualitative and quantitative methods, and a theoretical and practical approach. Thus, it was possible to implement the research in the multinational company analyzed, and to measure the benefits obtained.